Diskresi Kepolisian Diluar Pengadilan dalam Rangka Penyelesaian Perkara Pencurian oleh Anak dalam Keluarga - Dody Hendra Hendra (Universitas Negeri Surabaya, 2020)
Constitution of the Republic Indonesia 1945 states that Indonesia is a state of law. It is affirmed that the Republic of Indonesia is based on law (rechstaat), not for power merely (machtstaat). Children are the next generation of the nation that must be protected by their rights, so that if there is a criminal act involving children, it should not end in a prison sentence but can be settled in a certain way outside the court. Based on the consideration, the author disscuses this journal with the title